SPATIAL GENETIC VARIATION IN HOUSE FLY POPULATIONS, MUSCA DOMESTICA (DIPTERA : MUSCIDAE) - M. TRIPATHI; U.R. AGRAWAL; J. TRIPATHI; R.R. TEWARI (International Journal of Pharma and Bio Sciences, 2012)
Spatial genetic variation was assessed in the common house fly Musca domestica. Allozymes at three gene enzyme system unraveled ten loci which revealed seventeen alleles in house fly populations. F statistics revealed that except ACPH-1 and EST-3 all the other loci show inbreeding (Fis>Fst). Persistent heterozygosity was observed in ACPH-1(Fis= -0.140) which indicate random mating for this locus.